Multimorbidity patterns and association with mortality in 0.5 million Chinese adults. Issue 6 (20th March 2022) - Fan, Junning; Sun, Zhijia; Yu, Canqing; Guo, Yu; Pei, Pei; Yang, Ling; Chen, Yiping; Du, Huaidong; Sun, Dianjianyi; Pang, Yuanjie; Zhang, Jun; Gilbert, Simon; et al.
Abstract: Background: Few studies have assessed the relationship between multimorbidity patterns and mortality risk in the Chinese population. We aimed to identify multimorbidity patterns and examined the associations of multimorbidity patterns and the number of chronic diseases with the risk of mortality among Chinese middle-aged and older adults. Methods: We used data from the China Kadoorie Biobank and included 512, 723 participants aged 30 to 79 years. Multimorbidity was defined as the presence of two or more of the 15 chronic diseases collected by self-report or physical examination at baseline. Multimorbidity patterns were identified using hierarchical cluster analysis. Cox regression was used to estimate the associations of multimorbidity patterns and the number of chronic diseases with all-cause and cause-specific mortality. Results: Overall, 15.8% of participants had multimorbidity. The prevalence of multimorbidity increased with age and was higher in urban than rural participants. Four multimorbidity patterns were identified, including cardiometabolic multimorbidity (diabetes, coronary heart disease, stroke, and hypertension), respiratory multimorbidity (tuberculosis, asthma, and chronic obstructive pulmonary disease), gastrointestinal and hepatorenal multimorbidity (gallstone disease, chronic kidney disease, cirrhosis, peptic ulcer, and cancer), and mental and arthritis multimorbidity (neurasthenia, psychiatric disorder, and rheumatoid arthritis). During a median of 10.8 years of follow-up, 49, 371 deaths occurred. Compared with participants without multimorbidity, cardiometabolic multimorbidity (hazard ratios [HR] = 2.20, 95% confidence intervals [CI]: 2.14 − 2.26) and respiratory multimorbidity (HR = 2.13, 95% CI:1.97 − 2.31) demonstrated relatively higher risks of mortality, followed by gastrointestinal and hepatorenal multimorbidity (HR = 1.33, 95% CI:1.22 − 1.46). The mortality risk increased by 36% (HR = 1.36, 95% CI: 1.35 − 1.37) with every additional disease. Conclusion: Cardiometabolic multimorbidity and respiratory multimorbidity posed the highest threat on mortality risk and deserved particular attention in Chinese adults.